Simple, robust methods for high-throughput nanoliter-scale DNA sequencing - Smailus, Duane E.; Marziali, Andre; Dextras, Philip; Marra, Marco A.; Holt, Robert A. (Genome Research, 2005)
We have developed high-throughput DNA sequencing methods that generate high quality data from reactions as small as 400 nL, providing an approximate order of magnitude reduction in reagent use relative to standard protocols. Sequencing of clones from plasmid, fosmid, and BAC libraries yielded read lengths (PHRED20 bases) of 765 ± 172 (n = 10,272), 621 ± 201 (n = 1824), and 647 ± 189 (n = 568), respectively. Implementation of these procedures at high-throughput genome centers could have a substantial impact on the amount of data that can be generated per unit cost.